Study of the Effectiveness of Microcredit Program for Rice Paddy Business Development in Palangga Sub-district South Konawe Regency - Andi Nurul Syahrial; Azhar Bafadal; Yusna Indarsyih (International Journal of Technology and Education Research, 2024)
This study aims to determine the effectiveness of Microcredit and the income differences of agribusiness actors before and after receiving the microcredit program in Palangga District, South Konawe Regency. Effectiveness in this study uses three aspects: the amount of credit, credit utilization, and credit burden. The population in this study is all agribusiness actors who are customers and borrow microcredit in Kiaea Village and Persiapan Wonua Morini Village, Palangga District, totaling 40 people. Sampling was done using non-probability sampling methods through saturation sampling (census), where all populations were sampled. Data analysis used simple statistical analysis to measure the effectiveness of microcredit and Paired Sample t-test for income difference analysis. The results showed that the overall effectiveness of microcredit distribution is very effective, as seen from each variable, namely: 1) the amount of credit is very effective, 2) credit utilization is very effective, and 3) credit burden is very effective. There is an income difference for agribusiness entrepreneurs before and after receiving microcredit